Effect of Multi-Pass Bending Deformation on Microstructure Evolution and Mechanical Properties of AZ31 Alloy Sheet - Yang,Qingshan (2016)
The rolled AZ31 Mg alloy sheets were processed by multi-pass bending (MPB) process at room temperature and followed by annealing treatment. Mechanical properties of the as-received and MPB sheets in annealed conditions were examined based on the concurrent microstructure and texture evolution. The results show that the room temperature ductility of the Mg sheets was improved by multi-pass bending process. Moreover, the (0002) basal texture was drastically weakened. Enhanced the ambient mechanical properties, such as lower yield strength and larger uniform elongation, were fabricated by MPB path due to the weak basal texture. The microstructure and mechanical responses were characterized and discussed.